Magnetic Levitation Technology for Precision Motion Systems: A Review and Future Perspectives - Zhou, Lei; Wu, Jingjie (International journal of automation technology, 2022)
Precision motion systems are the core of a wide range of manufacturing equipment and scientific instruments, and their motion performance directly determines the quality and speed of the associated manufacturing or metrology processes. Magnetically levitated precision motion systems, where the moving target is supported by magnetic forces and without any mechanical contact, provide advantages of frictionless motion, vacuum compatibility, and contamination-free operation. These features endow the magnetic levitation technology with the capability to deliver excellent overall performance for precision positioning systems. Through decades of research and engineering efforts, significant advances have been made in the actuation, sensing, design, and control of magnetically levitated precision motion systems. This paper provides an introduction to the fundamentals of the feedback control, actuation, and sensing for the magnetic levitation technology, and provides a comprehensive literature review of various magnetically levitated precision positioning systems developed over the past three decades. The final part of this paper identifies several challenges in the design and control of today’s precision motion systems using magnetic levitation and provides an outlook on the possible directions for future research and development.